Satisfacción del cliente a los servicios crediticios ofertados por las cooperativas financieras del Tolima-Colombia (2023)
The credit services represent a multidimensional variable that influence the perception of value by the associates of the cooperative organizations. The main objective of this work is to establish the level of satisfaction of the associates of the financial cooperatives of the department of Tolima (Colombia), from the credit services that they offer. The research was developed under a quantitative approach; the scope is descriptive, with no experimental design. The population under study was constituted by eight (8) financial entities belonging to the cooperative sector. The instrument administered was the survey, which related factors such as the interest rate, the agility of the advisors, the credit requirements and the friendliness of the advisor. The most representative finding concerns the high degree of acceptance revealed by the cooperative members analyzed, which is the basis for making strategic decisions, not only from the marketing perspective, but at the corporate level. In order to reach a superlative level of positioning in the financial market, it is suggested to persist in the managerial techniques that have led to the achievements obtained in terms of user satisfaction. © 2018, Universidad del Zulia. All rights reserved.